Analysis of Resource Productivity and the Level of Fertilizer - Manure Substitution Among Vegetable Farmers in the Southern Region of Nigeria - Akpan, Sunday B.; Udoh, Edet J.; Bassey, Ememobong E.; Inya-agha, Chukwuemeka; Udo, Friday J. (Mediterranean Journal of Social Sciences, 2012)
The study analyzed farm input productivity and estimated constant elasticity of substitution of fertilizer for manure forvegetable farmers in the southern region of Nigeria. Primary data obtained from four hundred and eighty vegetable farmers inUyo and Itu regions of the southern part of Nigeria were used in the study. A combination of analytical tools including descriptivestatistics (percentages, frequency and tables), and regression analysis were used for data analysis. The generalized constantelasticity of substitution function was specified and estimated through a system of coefficients relationship after which theconstant elasticity of substitution of fertilizer for manure for each crop enterprise was calculated. The empirical results revealed aconstant elasticity of substitution of fertilizer for manure of about 27.21% for waterleaf production and 35.11% for fluted pumpkinproduction in the region. The Cobb-Douglas production function for waterleaf production revealed that planting material, familylabor, fertilizer, manure, and water have significant influenced on waterleaf production; while the linear production function forfluted pumpkin production revealed that seed, hired labor, fertilizer, and manure have significant impact on the quantity of flutedpumpkin produced. The result also revealed that the utilization of all significant production inputs of the two crop enterpriseswere in the rational zone of the classical production surface. A mean total factor productivity of 45.60% and 45.59% wererealized for waterleaf and fluted pumpkin farms respectively in the region. The study however recommended that governmentshould increase fertilizer supply to vegetable farmer at a subsidized rate, intensify effort towards increasing research on manureproduction to adequately complement the use of fertilizer and make land more accessible to vegetable crop farmers in theregion. Also, farmers cooperative organizations should be encourage among vegetable farmers as this would make inputsacquisition less cumbersome.